Factors influencing exclusive breastfeeding duration in South Sulawesi-Indonesia: A population-based cross-sectional study - Dinda Asari Zulkarnain; Rini Fitriani; Saharuddin Saharuddin; Andi Irhamnia Sakinah; Dahlan Dahlan (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Exclusive breastfeeding means that the infant receives only breast milk without any additional food or drink given which is started from the day 1 to 6 months old. Breast milk has been considered to be the greatest food source for babies as it contains various substances and antibodies that are important for baby's growth and development. Purpose: To investigate the factors influencing exclusive breast feeding on mothers at Dahlia Health Center of Mariso District, Makassar, South Sulawesi.Method: The observational study design by using cross sectional approach. The population of this study was mothers with children aged between 6- 24 months in the working area of Dahlia Health Center in 2020. The total population was 343 mothers. The sampling technique used in study was purposive sampling with a total sample of 80 people.The research data were analysed by using SPSS application with a Chi square test.Results: The findings of this study indicated various results on different variables. It was shown that p value was 0.030 (<0.05) for the variable of mothers’ age; p value was 0.009 (<0.05) for the variable of mothers’ education; p value was 1,000 (> 0.05) for the variable of mothers’ employment; p value was 0.538 (> 0.05) for the variable of family income; p value was 0.037 (<0.05) for the variable of mothers knowledge on exclusive breastfeeding; and p value was 0.000 (<0.05) for the variable of family support. Conclusion: From these results, it could be concluded that there are relationships between the variables of mothers’ age, education, work, family income, knowledge, and family support and the commitment of mother to breastfeed their children.